Kontainer larva Aedes sp. Di desa saung naga Kabupaten ogan komering ulu sumatera selatan tahun 2012 - I Gede Wempi Dody Surya Permadi (Loka Litbang Kesehatan Pangandaran, 2013)
The Dengue Fever (DF) is an infectious disease caused by virus hemorrhagic fever with the incubation disease is expected to 7 days, more or less which strikes the part of many people in all that territory. Tanjung Agung Public Health Centre which located in densely populated location being have greater possibility in morbidity disease and growing proliferation of a vector disease. The im of study was to find out the number of free larvae in the village of Saung Naga, district Ogan Komering Ulu in 2012. A spot survey was randomly assigned to 100-houses in Kampong IV. A single larvae method was used to gather House Index, Container Index, and Breteau Index data. In 2012, rate of HI was 11%, CI was 13% and BI was 5%, respectively. Bath tube was the form of container that consists of largest positive larvae Aedes sp. in Saung Naga village, sub-district of West Baturaja, South Sumatera. It discovered HI, CI, BI was declined and free larvae index was increased from 65% to 89%, almost close to 95%. It showed that most frequently found container was bathroom tubs (60.71%) and plastic (28.58%).